Implementing an intrahospital transport preparation (IHT) and management project for critically ill patients: identification of barriers and facilitators using consolidated framework for implementation research (CFIR) – a qualitative study - Jing Wang; Li Ma; Ying Lu; Baohua Li; Xiaotian Zhang; Rui Xie; Guifen Li; Man Cui; Lanfang Du (BMJ Open)
Objective To investigate the factors contributing to or hindering intrahospital transport preparation and management projects using the consolidated framework for implementation research (CFIR) framework.Design Semistructured interviews were used in a qualitative descriptive study.Setting This study was conducted in the emergency room of a tertiary hospital in Beijing, China, between December 2023 and January 2024.Participants Purposive sampling was employed to recruit 22 doctors and nurses involved in intrahospital transport.Primary and secondary outcome measures A content analysis technique was employed to transcribe and analyse all gathered data. Iterative methods were used for the data collection and analysis.Results 39 implementation determinants—11 barriers, 25 facilitators and 3 neutral factors—were identified. These determining factors aligned with 23 of the 26 CFIR constructs and 5 CFIR domains. Facilitators were identified in four primary domains: ease of implementation, scientific and project completion, patient advantages and enhanced capacity for safe and professional transfer. Additionally, hurdles were identified in the CFIR domains of intervention characteristics, outer settings and inner settings. These barriers include inadequate training and mobilisation, insufficient information systems, unclear reward and punishment policies, a shortage of labour and material resources and the absence of established reward and punishment laws.Conclusion This study identified the factors influencing the emergency department’s intrahospital transport planning and management project implementation. Despite numerous obstacles, the project provides a clear pathway for advancing intrahospital transport planning and management.